Anatomia de uma empresa militar e de segurança privada: a empresa DynCorp em perspectiva global - Paoliello, Tomaz [UNESP] (2016)
Private military and security companies (PMSC) is a new actor that has attracted great attention in the debates within the International Relations discipline. Through the study of a particular north-american company, DynCorp, we seek to investigate the nature of these actors in the great process of globalization. The literature on PMSC usually presents the idea that the emergence of such players has occurred through spontaneous supply and demand forces. The hypothesis that assist this idea is that the states are moving away from the new wars. Here this hypothesis is challenged and replaced by another. The State, particularly the US, has adapted its engagement in capacity in conflicts by engaging the PMSC, and stimulating the growth of a private security market. DynCorp is part of this movement. We investigate the relationship of co-constitution, in which companies and state are organized to develop the new "market for force", and the birth of PMSC as actors of a hybrid nature, associated with the transformation of the neoliberal state. The study of DynCorp unfolds in three dimensions: its corporate face, as a transnational company associated with market principles; a fighting face, as one of the new actors on the stage of contemporary conflicts; and as a constituent part of a foreign policy apparatus, associated with their only customer, the United States government.